Improving bank erosion modelling at catchment scale by incorporating temporal and spatial variability. Issue 1 (12th April 2017) - Janes, Victoria; Holman, Ian; Birkinshaw, Stephen; O'Donnell, Greg; Kilsby, Chris
Abstract: Bank erosion can contribute a significant portion of the sediment budget within temperate catchments, yet few catchment scale models include an explicit representation of bank erosion processes. Furthermore, representation is often simplistic resulting in an inability to capture realistic spatial and temporal variability in simulated bank erosion. In this study, the sediment component of the catchment scale model SHETRAN is developed to incorporate key factors influencing the spatio‐temporal rate of bank erosion, due to the effects of channel sinuosity and channel bank vegetation. The model is applied to the Eden catchment, north‐west England, and validated using data derived from a GIS methodology. The developed model simulates magnitudes of total catchment annual bank erosion (617–4063 t y ‐1 ) within the range of observed values (211–4426 t yr ‐1 ). In addition, the model provides both greater inter‐annual and spatial variability of bank eroded sediment generation when compared with the basic model, and indicates a potential 61% increase of bank eroded sediment as a result of temporal flood clustering. The approach developed within this study can be used within a number of distributed hydrologic models and has general applicability to temperate catchments, yet further development of model representation of bank erosion processes is required. © 2017 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd.